High pressure chronic retention. Issue 6380 (4th June 1983) - George, N J; O'Reilly, P H; Barnard, R J; Blacklock, N J
Abstract : In a prospective study of high pressure chronic retention, a newly defined disorder of the urinary tract, 21 patients were analysed for their mode of presentation and urodynamic, renographic, and operative findings. High pressure chronic retention is characterised by late onset enuresis, a tense, palpable bladder, hypertension, and progressive renal impairment associated with bilateral hydronephrosis and hydroureter commonly leading to uraemia and death. Obstructive urological symptoms are typically absent in uncomplicated cases. The study confirmed that patients with the disorder are commonly elderly and present, not necessarily to a urologist, with late onset enuresis or symptoms of cardiac decompensation. After transurethral resection the patients, if correctly managed, may be expected to make a satisfactory recovery.